Gematon: Living and Dying in a Kushite Town on the Nile - Sjöström, Isabella Welsby (2024)
This volume presents the pottery from Sudan Archaeological Research Society excavations at the site of Kawa, Northern Dongola Reach, between 1997 and 2018, fully illustrated with photographs and line drawings. This is the third in the series focusing on the fieldwork conducted at this important site. Volume III presents a comprehensive catalogue of the pottery found across the site, focusing on the forms, decoration, marks and fabric, as well as incorporating a discussion of the character of relevant areas. This includes a detailed discussion of the Napatan amphorae found in Building F1 and the cemetery remains at R18. The material at Kawa represents a unique collection of contextualised material invaluable for reconstructing activity patterns in this region during the Napatan and Meroitic periods and contributing towards an increased understanding of this time period.